2007
DOI: 10.1183/09031936.00064807
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-oesophageal reflux and gastric aspiration in lung transplant patients with or without chronic rejection

Abstract: Acid gastro-oesophageal reflux (GOR) and gastric aspiration have been labelled as risk factors for chronic rejection bronchiolitis obliterans syndrome (BOS) after lung transplantation (LTx). The present study aimed to further characterise GOR (both acid and nonacid) and the degree of gastric aspiration in LTx recipients both with and without BOS.Impedance-pH recordings were used for GOR detection. Pepsin and bile acid levels were measured in bronchoalveolar lavage fluid (BALF).A total of 48% of patients had in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
202
4
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(217 citation statements)
references
References 25 publications
6
202
4
5
Order By: Relevance
“…К дополни тельным факторам риска относятся вирусные [29,31,32,[56][57][58][59][60][61][62][63][64], бактериальные [65][66][67][68] и грибковые инфекции [69][70][71]. Цитомегаловирусной инфекцией поражаются как врожденный, так и адаптивный компоненты иммунитета и стимулируется выработ ка антигенов HLA I и II классов на эпителиальных клетках [72,73], а также стимулируется и усиливает ся аллогенный иммунный ответ и синтез провоспа лительных цитокинов [72,74].…”
Section: рекомендацияunclassified
“…К дополни тельным факторам риска относятся вирусные [29,31,32,[56][57][58][59][60][61][62][63][64], бактериальные [65][66][67][68] и грибковые инфекции [69][70][71]. Цитомегаловирусной инфекцией поражаются как врожденный, так и адаптивный компоненты иммунитета и стимулируется выработ ка антигенов HLA I и II классов на эпителиальных клетках [72,73], а также стимулируется и усиливает ся аллогенный иммунный ответ и синтез провоспа лительных цитокинов [72,74].…”
Section: рекомендацияunclassified
“…Pepsin is found in BALF of almost all lung transplant patients and bile acids in half of the lung transplant patients. [24] It is not yet known which component of the refluxate is the most harmful to bronchial epithelial damage.…”
Section: Pathophysiology Of Reflux-related Coughmentioning
confidence: 99%
“…In contrast, patients with severe lung disease often have unrecognised pathological reflux. In one study of 65 consecutive IPF patients, 87% had pathological gastro-oesophageal reflux (GER) [12], another study reported GERD in 48-76% of patients following lung transplantation [13][14][15]. Microaspiration is more likely in the setting of impaired swallowing mechanism and depressed alertness, conditions more prevalent in the elderly, as suggested by one study [16] which showed an association of bilateral chest radiography scarring with pH probe-proven GERD in elderly patients referred for evaluation of gastrointestinal symptoms.…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…Factors predisposing to GERD-related lung disease in this population include gastroparesis [81], vagus nerve dysfunction, a high incidence of post-operative oropharyngeal dysphagia [82], and depressed cough reflex due to the lack of innervation of the allograft [83]. Most lung transplant patients with GERD lack classic symptoms [14], and although acid suppression therapy is frequently given to this patient group, non-acid reflux is present in up to 50% as documented by the finding of bile acids in lung lavage samples [13], a finding associated with BOS in one study [84]. Supporting the aetiological role of GERD in a subset of BOS patients, DAVIS et al [85] NTM infection NTM infection of the lung may produce a clinical picture of nodular bronchiectasis in nonsmokers [86], and this disease has been associated with oesophageal disorders [87][88][89].…”
Section: Bronchiolitis Obliterans In Lung Transplant Recipientsmentioning
confidence: 99%
See 1 more Smart Citation